Freshwater and sediment data of the entire Ems river and its tributaries sampled during summer 2016 - Daniel Pröfrock; Tristan Zimmermann; Johanna Irrgeher; Andrea Pieper; Hans-Burkhard Erbslöh; Florian Dutschke (PANGAEA, 2022)
In order to understand and map the complex mass transport pathways and possible transformation processes of contaminants in coastal regions such as the German Bight, the main contributors must be identified and evaluated. In this context, rivers represent a major input source. In the framework of a river campaign from 20.06.16 till 25.06.2016, sediment and freshwater samples of the Ems and its tributaries were taken to determine their elemental and isotopic fingerprint and to investigate possible inputs into the German Bight.